2019
DOI: 10.1108/jbim-09-2017-0223
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring characteristics and functions: mentoring’s influence on salespeople

Abstract: Purpose This paper aims to examine a longitudinal study of mentoring functions and their effect on salesperson attitudes and intentions. Design/methodology/approach The research is based on a multi-year study of salespeople beginning when the salesperson entered the industry being examined. Findings The level of interaction between the mentor and protégé was found to be the only antecedent examined that related to the perceived quality of mentoring functions. Age, education and length of employment for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Experience-based characteristics include educational background, career experience, and geographic location (Eby et al, 2013). Our search revealed one recent study examining experiential similarity and mentoring support: surveying a sample of newly hired insurance salespeople over a 5-year period and their mentors, Brashear-Alejandro et al (2019) found that the degree of similarity between education levels LODJ 43,3 of the mentor and prot eg e was not a significant predictor of instrumental support or psychological and social support. To clarify this relationship using studies drawn from youth, academic, and workplace mentoring contexts, Eby et al's (2013) meta-analysis provides a comprehensive quantitative review of the predictors of perceived mentoring support received and relationship quality.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Experience-based characteristics include educational background, career experience, and geographic location (Eby et al, 2013). Our search revealed one recent study examining experiential similarity and mentoring support: surveying a sample of newly hired insurance salespeople over a 5-year period and their mentors, Brashear-Alejandro et al (2019) found that the degree of similarity between education levels LODJ 43,3 of the mentor and prot eg e was not a significant predictor of instrumental support or psychological and social support. To clarify this relationship using studies drawn from youth, academic, and workplace mentoring contexts, Eby et al's (2013) meta-analysis provides a comprehensive quantitative review of the predictors of perceived mentoring support received and relationship quality.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…These functions provided by a developmental network help individuals with their career success. For example, career support was found to have a statistically significant relationship with career satisfaction (Kammeyer-Mueller & Judge, 2008; Kay & Wallace, 2009); psychosocial support with career commitment, organizational and team commitment, intention to leave, and wage (Brashear-Alejandro et al, 2019; Higgins et al, 2010); and role modeling with organizational commitment (Haran & Jeyaraj, 2019; Lankau & Scandura, 2002).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Third, satisfaction with training reflects salespeople's subjective evaluation of training activities. Training programs must improve personal well-being and business skills (Loveland et al, 2015;Brashear-Alejandro et al, 2019). Successful training programs enhance explicit and tacit knowledge, continuous learning, personal growth, effectiveness and efficiency.…”
Section: Trainingmentioning
confidence: 99%